Situation Report: Bulgaria, 7 March 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Sofia Dailies to Help Save Newsprint Problems with Automated Management Systems Bulgarian Ambassador to the FRG Appointed Yugoslav Polemics over Macedonian Minority in Bulgaria Further BCP Support for World Communist Conference